Salinity-Growth Response and Ichthyotoxic Potency of the Chilean Pseudochattonella verruculosa - Mardones, Jorge I.; Fuenzalida, Gonzalo; Zenteno, Katherine; Alves-de-Souza, Catharina; Astuya, Allisson; Dorantes-Aranda, Juan José (Frontiers in Marine Science, 2019)
Despite salmon farmers suffering the worst damage from a harmful algal bloom in Chile’s history (US$800M) due to a massive outbreak of the dictyochophyte Pseudochattonella in 2016 (~7000-20,000cellsml-1), the effect of environmental drivers and the potency of lytic toxins produced by the local clones of this species remain still largely unexplored. Based on the drastic oceanographic anomalies observed in the Chilean fjords during the 2016-El Niño“Godzilla”event, the role of salinity(15to35psu) on Pseudochattonella cell growth and cytotoxicity was studied by culturing, scanning-electron-microscopy(SEM) and using a rainbow trout cell line RTgill-W1 assay to define:(1)vegetative growth rates, (2)cell taxonomy, (3)ichthyotoxicity of monoclonal cultures at 25 and 35 psu in salinity, (4)differences in toxicity of lysed cells and supernatant at different cell concentrations (from 10to100,000cells ml-1) and (5)temporal stability of lytic compounds. This study formally confirms the presence of P.verruculosa in Chilean waters using the large subunit(LSU) of the nuclear ribosomal RNAgene. The Chilean ARC498-strain showed maximum cell densities at 30 psu (max. 84,333±4,833cellsml-1) and maximum growth rates (max) at 20 psu (1.44cellsd-1). Cultures at 15psu showed suppressed maximum cell density (max.269±71cellml-1) but high max were recorded at the beginning of the exponential growth (1.31cells d-1). No significant differences were observed between lysed cells and supernatant treatments in the two salinity levels, suggesting that the most lytic portion is released into the cell-free media instead of remaining cell bound. Cytotoxicity was correlated to cell abundance, reducing gill cell viability down to 80 and 65% compared to controls at 10,000and100,000cells ml-1, respectively. Unexpectedly, lytic compounds from ARC498 strain at 35psu showed to be less toxic than cultures at 25, where a noticeable presence of peripheral mucocysts were observed by SEM. Lytic compounds from In-Vitro experiments are weakly toxic even at high cell concentrations, highly unstable and rapidly degraded in the light after5 days of storage at15°C. Our results point to the important effect of salinity on growth and ichthyotoxic potency of Pseudochattonella and highlight the need for a deeper insight into the role of mucocysts in fish gill damage, which would provide a greater understanding as to the harmful modes of action of this species.